Rumensin helps to reduce the incidence and severity of legume bloat in cattle - Nagaraja, Tiruvoor G.; Katz, M.P.; Fina, L.R. (Kansas Agricultural Experiment Station, 2012)
Monensin at 300 mg and 450 mg per 1000 lbs body weight reduced the severity of alfalfa pasture bloat by 41.2 and 73.1 %, respectively. Lasalocid at the same levels reduced the bloat score by 25.5 and 12.4%. The difference between the two antibiotics appears to be in their ability to inhibit rumen protozoa. Monensin reduced protozoal population in the rumen, whereas lasalocid had no effect. A smaller protozoal population decreases compounds that contribute to frothiness and also increases substances such as plant chloroplasts, which have antifrothing properties.
Keywords: Dairy; Rumensin; Bloat; Protozoa; Alfalfa